2017
DOI: 10.12669/pjms.336.13224
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Uric Acid Level and Microalbuminuria in Type-2 Diabetic Nephropathy

Abstract: Objective:To measure the correlation between microalbuminuria and serum uric acid level in Type-2 diabetic nephropathy.Methods:This cross-sectional study was done in department of Medicine, Mayo hospital Lahore from August 2014 to February 2015. A total of 200 patients with Type-2 diabetic nephropathy were enrolled in the study. Demographic data and contact details were obtained. Serum Uric acid and microalbuminuria by albumin to creatinine ratio (ACR) in random urine sample was measured at the time of inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Therefore, UA levels are associated with the occurrence and development of DN and are independent risk factors for early kidney disease [72, 73], which help to predict microalbuminuria progression [74]. Serum UA and microalbuminuria levels were significantly positively correlated with renal disease in patients with T2DM [75]. Patients with higher SUA levels have poorer renal function, independent of glycated hemoglobin (HbA1c) or the duration of diabetes [76].…”
Section: Epidemiology Studiesmentioning
confidence: 99%
“…Therefore, UA levels are associated with the occurrence and development of DN and are independent risk factors for early kidney disease [72, 73], which help to predict microalbuminuria progression [74]. Serum UA and microalbuminuria levels were significantly positively correlated with renal disease in patients with T2DM [75]. Patients with higher SUA levels have poorer renal function, independent of glycated hemoglobin (HbA1c) or the duration of diabetes [76].…”
Section: Epidemiology Studiesmentioning
confidence: 99%
“…Several studies have reported [29] that fenofibrate could inhibit the renal organic anion transporter urate transporter 1 and increase urinary excretion of UA to decrease serum UA levels. Several studies [30][31][32] have shown that serum UA and microalbuminuria are significantly positively associated in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many diabetes complications appear with the progress of disease and correlated with the duration of disease including coronary artery diseases, nephropathy, retinopathy, and neuropathy (Kobayashi et al 2020). As the duration of disease prolonged, the serum level of many biomarkers including uric and microalbuminuria (Latif et al 2017) indicating the progression of nephropathy with time. Therefore, this is a good point to consider CLNK as a predictor for a complication that needs more investigation.…”
Section: Discussionmentioning
confidence: 99%